Fuzzy vs Nonfuzzy in 2D Visual Servoing for Robot Manipulators. (7th February 2013) - Bueno-López, Maximiliano; Arteaga-Pérez, Marco A.
In this paper we consider the tracking control problem of planar robots manipulators via visual servoing in the presence of parametric uncertainties associated with the robot dynamics and the camera parameters. An image–based visual servo control is developed using a Takagi–Sugeno (T–S) fuzzy model. The design includes an image coordinate velocity observer. To the best knowledge of the authors such a proposal remains hitherto unpublished. The new scheme is compared experimentally with two different non–fuzzy algorithms showing the good performance and advantages of the complete system.